2020
DOI: 10.1016/j.tranon.2019.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Independent Role of TERT and NF1 in High Grade Gliomas?

Abstract: BACKGROUND: High grade glioma molecular profiling is of particular interest in neurooncology. The role of telomerase reverse transcriptase (TERT) varies dependent upon other molecular parameters. We explored the role of TERT in 101 high-grade gliomas. METHODS: A total of 101 patients (pts) with grade III–IV gliomas treated with standard of care and informative tumor genotypes were included in the present study. Of 55 genes targeted with the next-generation sequencing panel, mutations (muts) were found in 37; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Whether TERTp mutation status is an independent prognostic factor is highly controversial. Numerous studies have highlighted the potential negative independent prognostic impact of TERTp mutations [ 18 , 19 , 20 , 21 , 24 , 25 , 61 , 62 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], whereas others [ 14 , 17 , 51 , 53 , 56 , 63 , 64 , 65 , 75 , 76 ] have suggested that the deleterious impact of TERTp mutation is correlated to the presence of cofounding molecular and clinical factors such as older age, IDH-wt status, and unmethylated MGMTp status. The MGMT gene codes for a protein involved in the DNA repair system.…”
Section: Resultsmentioning
confidence: 99%
“…Whether TERTp mutation status is an independent prognostic factor is highly controversial. Numerous studies have highlighted the potential negative independent prognostic impact of TERTp mutations [ 18 , 19 , 20 , 21 , 24 , 25 , 61 , 62 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], whereas others [ 14 , 17 , 51 , 53 , 56 , 63 , 64 , 65 , 75 , 76 ] have suggested that the deleterious impact of TERTp mutation is correlated to the presence of cofounding molecular and clinical factors such as older age, IDH-wt status, and unmethylated MGMTp status. The MGMT gene codes for a protein involved in the DNA repair system.…”
Section: Resultsmentioning
confidence: 99%
“…This would be a rather unusual molecular constellation for pilocytic astrocytoma. Instead, combined mutations in TERTp , PTEN and NF1 are described for high-grade gliomas and are associated with an unfavorable prognosis [ 35 , 36 ]. Not surprisingly, this patient suffered from tumor progression at already 9 months after the first surgery, despite gross total resection.…”
Section: Resultsmentioning
confidence: 99%
“…These two genes play a critical role in the progression of GBM. It has been shown that mutations of NF1 , a tumor suppressor gene, are quite common in the mesenchymal molecular subtype, which has a very poor prognosis due to aggressive biological behavior ( 60 , 74 ). Patients with GBM who have an activated phosphatidylinositol 3-kinase (PI3K) signaling pathway also have poorer outcomes than those who do not ( 75 ).…”
Section: Development Of Radiomics Prediction Modelsmentioning
confidence: 99%